A micrometer-sized active pharmaceutical formulation and a method for preparing the same

By combining active drugs with biomass porous adsorbents, oil dispersants, and coating agents, the stability and release problems of micron-sized hydrophobic active drug formulations in existing technologies have been solved, achieving improved stability and release effects in tablets and aqueous solutions.

CN121081667BActive Publication Date: 2026-08-25JIAXING DINGSHENG HEALTH TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511137647.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2026-08-25
Estimated Expiration
2045-08-14

AI Technical Summary

Technical Problem

Existing technologies are insufficient for preparing active pharmaceutical formulations that are stable, resistant to high temperatures and humidity, and micron-level hydrophobic in specific application scenarios such as tablets and aqueous solutions, thus failing to meet storage and processing requirements.

Method used

Micron-sized active pharmaceutical formulations are prepared by combining active drugs, biomass porous adsorbents, oil dispersants, and coating agents through mixing, adsorption, and coating processes. The component ratios and process sequence are optimized to improve stability and release efficiency.

Benefits of technology

The prepared micron-sized active pharmaceutical formulation exhibits good stability in tableting and aqueous environments, demonstrates good digestion and release effects, and improves bioavailability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121081667B_ABST
    Figure CN121081667B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of pharmaceutical preparation, in particular to a kind of micron active pharmaceutical preparation and preparation method thereof.The micron active pharmaceutical preparation includes active drug, biomass porous adsorbent, oil dispersant and coating agent, the active drug is low melting point fat-soluble drug, high melting point fat-soluble drug or water-soluble drug;The oil dispersant is the mixture of edible oil and oil gel agent, and the mass ratio of the two is 1:0.1-1.The active pharmaceutical preparation obtained by the present application is micron hydrophobic dosage form, and the tabletting and water environment processing stability are good, and have ideal digestive release effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical formulation technology, specifically to a micron-sized active pharmaceutical formulation and its preparation method. Background Technology

[0002] Drug functional factors (also known as active drugs) refer to active ingredients in drugs that have specific physiological regulatory or therapeutic effects, including natural extracts or artificially synthesized substances, which can achieve therapeutic effects by targeting cell signaling pathways, gene expression, etc.

[0003] There are two main classification methods for functional factors: classification based on their chemical structure and classification based on their physiological function. Classification based on chemical structure mainly includes: active polysaccharides, functional oligosaccharides, functional monosaccharides and disaccharides, functional lipids, sugar alcohols, polysaccharides, active polypeptides and proteins, vitamins and vitamin analogs, functional minerals and trace elements, plant active ingredients, and active bacteria, etc.

[0004] Pre-processing active pharmaceutical ingredients into micron-sized solid functional formulations of different dosage forms facilitates adaptation to diverse processing needs and improves human health. However, some active pharmaceutical ingredients exhibit poor stability, requiring the development of specialized formulation processes. For instance, folic acid, a water-soluble active pharmaceutical ingredient, is unstable in acidic solutions, relatively unstable to heat, and more easily degraded by light. Vitamin E, a low-melting-point fat-soluble drug, is highly sensitive to light, easily oxidized and decomposed, and is also susceptible to degradation due to environmental temperature and humidity. Paclitaxel, a high-melting-point fat-soluble drug, is prone to hydrolysis and breakage of its ester bonds in acidic or alkaline environments, leading to loss of activity. Furthermore, paclitaxel is prone to oxidative degradation and is highly sensitive to light and environmental temperature, readily degrading under ultraviolet light or high-temperature conditions.

[0005] Therefore, active pharmaceutical ingredients need to undergo certain treatments to improve their storage and processing stability.

[0006] Chinese patent publication CN1242168A discloses a method of adding antioxidants (sodium ascorbate), light stabilizers (phytic acid), and heat stabilizers (biomodified DD enzyme starch) along with folic acid to improve the retention rate of folic acid during high-temperature processing. However, simple mixing of solid materials cannot achieve dense protection of folic acid, resulting in the need for further improvement in the protective effect.

[0007] Chinese Patent Publication No. CN119112901A discloses a folic acid tablet with low oxidative impurities, comprising the following components: a mixture of folic acid and an antioxidant; porous starch; wherein the mass ratio of the folic acid and antioxidant mixture to the porous starch is (1-2):(3-4); and the mass ratio of folic acid to the antioxidant is 1:(1-3). In the preparation of this folic acid tablet, folic acid and the antioxidant tert-butylhydroquinone are mixed and then pulverized together. This ensures that the antioxidant fully encapsulates the folic acid, preventing or delaying its oxidation, and controlling the particle size of the mixture to be D90 < 5 μm. The mixture is then thoroughly mixed with the porous starch. Utilizing the porosity of the porous starch, folic acid and the antioxidant can be adsorbed into the pores of the starch, while reducing the contact between folic acid and oxygen and light, thereby reducing the generation of oxidative impurities during long-term storage and improving its high-temperature stability. However, the porous starch has poor adsorption effect on solid materials, and folic acid still dissolves rapidly in an aqueous environment, thus losing its protective effect.

[0008] Chinese Patent Publication No. CN117752620A discloses a folic acid tablet comprising folic acid, povidone, antioxidant, microcrystalline cellulose, mannitol, and dicalcium phosphate. The preparation process includes: (1) preparing a coating solution: mixing and dispersing folic acid, antioxidant, ethanol, and water to obtain a coating solution; (2) preparing a solid carrier: mixing microcrystalline cellulose, mannitol, and dicalcium phosphate and pulverizing them into particles of 50-100 micrometers to obtain a solid carrier; placing the solid carrier in a fluidized bed for coating; obtaining 50-100 micrometer coated folic acid particles through a sieve; and compressing the coated folic acid particles into tablets to obtain folic acid tablets. The stability of folic acid is improved by adding the above excipients and coating. However, this folic acid tablet places folic acid in the outer coating layer, resulting in poor stability of folic acid exposed on the surface.

[0009] Besides folic acid, Chinese patent publication CN110237046A discloses a method for preparing L-5-methyltetrahydrofolate microcapsules. This method first adds an aqueous solution of L-5-methyltetrahydrofolate to a shellac methanol solution, causing phase separation and precipitation, thereby encapsulating L-5-methyltetrahydrofolate in shellac to form a first layer of microcapsules. Then, a film-forming material, zein, and ethyl cellulose are used to encapsulate the first layer of microcapsules, resulting in L-5-methyltetrahydrofolate microcapsules with two layers of encapsulation, which can significantly improve the stability of L-5-methyltetrahydrofolate. Although this invention obtains microcapsules with better stability through double-layer encapsulation, the particles cannot achieve a uniform distribution at the micrometer level, and the coating layer still cannot completely block water molecule penetration.

[0010] Chinese Patent Publication No. CN118453533A discloses a method for preparing highly stable vitamin E soft capsules. The vitamin E soft capsules mainly consist of: coated vitamin E, vegetable oil, antioxidants, emulsifiers, hydroxypropyl starch, glycerin, and purified water. The preparation process of the coated vitamin E is as follows: vitamin E is added to anhydrous ethanol, mesoporous silica particles are added, and the mixture is stirred and centrifuged to obtain a composite material; a film-forming solution of nanocrystalline cellulose and hydroxypropyl starch is sprayed onto the surface of the composite material, and dried to obtain the coated vitamin E. This invention requires the pre-dissolving of vitamin E with solvents such as ethanol, resulting in harsh processing conditions and low loading capacity, and the surface coating layer cannot achieve complete hydrophobicity.

[0011] Chinese Patent Publication No. CN104586750A discloses a membrane-coated paclitaxel nanomedicine, prepared by combining aerosol atomization technology and spontaneous film-forming coating technology of complexes to improve the solubility and stability of paclitaxel in water. However, this invention, through coating, actually promotes the water solubility of paclitaxel, failing to meet the requirements for processing in aquatic environments.

[0012] The existing technologies described above improve the stability of active pharmaceutical ingredients by adding various excipients, coating, or microencapsulating them. However, in specific applications such as tablets and aqueous solutions, the active pharmaceutical ingredient needs to exist in the form of micron-sized hydrophobic particles. This is necessary to improve storage stability while also meeting processing requirements such as high temperature resistance, high humidity resistance, and solid mixing. Since existing technologies cannot achieve the technical goal of micron-sized hydrophobicity, formulation technology needs further improvement.

[0013] Therefore, it is essential to develop a micron-sized active pharmaceutical formulation and its preparation method that can solve the above-mentioned technical problems. Summary of the Invention

[0014] The purpose of this invention is to overcome the shortcomings of the prior art and provide a micron-sized active pharmaceutical preparation and its preparation method that has good stability in micron-level dispersion, tableting and aqueous processing, good digestion and release effect, and good hydrophobicity.

[0015] This invention is achieved through the following technical solutions: The first aspect of this invention provides a micron-sized active pharmaceutical formulation, comprising an active pharmaceutical ingredient, a biomass porous adsorbent, an oil dispersant, and a coating agent, wherein the active pharmaceutical ingredient comprises a low-melting-point lipid-soluble drug, a high-melting-point lipid-soluble drug, or a water-soluble drug; the low-melting-point lipid-soluble drug has a melting point ≤100℃, and the high-melting-point lipid-soluble drug has a melting point >100℃. The oil dispersant is a mixture of edible oil and oil gelling agent in a mass ratio of 1:0.1-1.

[0016] The edible oils include, but are not limited to, at least one of sesame oil, peanut oil, soybean oil, rapeseed oil, rice bran oil, sunflower seed oil, cottonseed oil, corn oil, tea oil, and flaxseed oil, with high melting point oils being preferred.

[0017] The oleogel is at least one of beeswax, rice bran wax, and carnauba wax.

[0018] In one embodiment of the present invention, when the active drug is a low-melting-point fat-soluble drug, the mass ratio of the active drug to the oil dispersant is 1:0.05-1.

[0019] In one embodiment of the present invention, when the active drug is a high-melting-point fat-soluble drug, the mass ratio of the active drug to the oil dispersant is 1:1-4.

[0020] In one embodiment of the present invention, when the active drug is a water-soluble drug, the mass ratio of the active drug to the oil dispersant is 1:0.5-5.

[0021] As one embodiment of the present invention, the low-melting-point fat-soluble drug includes at least one of vitamin E, vitamin D3, vitamin A, and fish oil.

[0022] In one embodiment of the present invention, the high-melting-point fat-soluble drug includes at least one of paclitaxel and β-carotene.

[0023] In one embodiment of the present invention, the water-soluble drug includes at least one of water-soluble B vitamins and vitamin C. The water-soluble B vitamins may be folic acid.

[0024] In one embodiment of the present invention, the biomass porous adsorbent includes at least one of porous starch, porous cellulose and porous zein, and the average particle size of the biomass porous adsorbent is 1-100 μm.

[0025] The porous starch can be formed from starch through enzymatic hydrolysis. The gelatinization temperature of starch is generally 60-70℃, therefore high amylose corn starch is preferred, with a gelatinization temperature greater than 100℃, making it more resistant to high-temperature water environments.

[0026] The porous cellulose can be formed by dissolving and regenerating microcrystalline cellulose.

[0027] The porous zein is prepared from zein through pelleting and enzymatic hydrolysis.

[0028] As one embodiment of the present invention, a low-melting-point fat-soluble drug can also be used as a dispersant to disperse a water-soluble drug.

[0029] In one embodiment of the present invention, the coating agent comprises at least one of chitosan, sodium alginate, and calcium chloride, ethyl cellulose, and zein. Each coating agent is applied by spraying in solution form.

[0030] Preferably, when the coating agent includes zein, the biomass porous adsorbent does not contain porous zein.

[0031] In one embodiment of the present invention, the mass ratio of the biomass porous adsorbent to the total mass of the active drug and the oil dispersant is 1:0.1-5.

[0032] In one embodiment of the present invention, the mass ratio of the coating agent to the active drug is 1-100:100.

[0033] In one embodiment of the present invention, the micron-sized active pharmaceutical preparation is a granule, tablet, capsule, or suspension.

[0034] A second aspect of the present invention provides a method for preparing the above-mentioned micron-sized active pharmaceutical formulation, comprising the following steps: (1) The active drug is mixed with an oil dispersant to obtain a liquid dispersion system; (2) The biomass porous adsorbent is mixed with a liquid dispersion system to obtain the adsorption product; (3) Prepare a coating solution with the coating agent, and use the coating solution to coat the adsorption product obtained in step (2), and dry it to obtain the product.

[0035] The preparation method described above produces granules, which can be further processed to produce other dosage forms such as tablets, capsules, or suspensions.

[0036] As one embodiment of the present invention, in step (1), when the active drug contains a high melting point fat-soluble drug or a water-soluble drug, the active drug is further mixed with the oil dispersant and then ground to make the average particle size of the active drug reach 0.1-1 μm, and the liquid dispersion system has fluidity.

[0037] Preferably, the grinding temperature is 30-90℃ and the grinding time is 40-60 minutes.

[0038] In one embodiment of the present invention, the concentration of the coating solution in step (3) is 10-100% of the saturation concentration.

[0039] In one embodiment of the present invention, the coating process in step (3) is carried out in a fluidized bed.

[0040] As one embodiment of the present invention, after drying in step (3), the product is further processed into granules, tablets, capsules or suspensions. During the processing, pharmaceutically acceptable excipients that are beneficial to the formation of granules, tablets, capsules or suspensions may be added.

[0041] The beneficial effects of this invention are: This invention first mixes the active drug with an oil dispersant to regulate its particle size and dispersibility; then, the resulting liquid dispersion system is adsorbed using the porous structure of a biomass porous adsorbent, and after adsorption and natural cooling, the liquid dispersion system transforms into a stable oleogel; finally, a coating solution is used for coating treatment. The active drug formulation prepared through a specific sequence of processing steps is a micron-sized hydrophobic formulation with good stability in tableting and aqueous processing, low solubility in gastric juice, and almost complete dissolution in intestinal juice, exhibiting ideal digestive release effects and improving bioavailability.

[0042] This invention optimizes the composition and dosage ratio of the oil dispersant, or uses multi-layer coating, which can further improve the stability of tableting and processing in aqueous environments, while also enhancing digestion and release effects and increasing bioavailability. Attached Figure Description

[0043] Figure 1 This is a scanning electron microscope image of the porous starch from Example 1.

[0044] Figure 2 This is a scanning electron microscope image of the micron-sized folic acid formulation from Example 1.

[0045] Figure 3 This is a transmission electron microscope image of the micron-sized folic acid formulation from Example 1.

[0046] Figure 4 This is a scanning electron microscope image of the porous cellulose in Example 2.

[0047] Figure 5 This is a scanning electron microscope image of the micron-sized vitamin E preparation from Example 2.

[0048] Figure 6 This is a transmission electron microscope image of the micron-sized vitamin E preparation from Example 2.

[0049] Figure 7 This is a scanning electron microscope image of porous zein from Example 3.

[0050] Figure 8 This is a scanning electron microscope image of the micron-sized paclitaxel formulation from Example 3.

[0051] Figure 9 This is a transmission electron microscope image of the micron-sized paclitaxel formulation from Example 3.

[0052] Figure 10 This is a scanning electron microscope image of the micron-sized folic acid preparation from Example 1 after being subjected to pressure.

[0053] Figure 11 This is a scanning electron microscope image of the micron-sized vitamin E preparation of Example 2 after being subjected to pressure.

[0054] Figure 12 This is a scanning electron microscope image of the micron-sized paclitaxel formulation of Example 3 after being subjected to pressure. Detailed Implementation

[0055] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer as a result. However, these embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.

[0056] Example 1 0.3 kg of folic acid, 1 kg of sunflower seed oil, and 0.1 kg of rice bran wax were ground at 80°C for 45 minutes to obtain a liquid dispersion system. Then, 3 kg of porous starch was added to the liquid dispersion system for adsorption. After complete adsorption, a 1% (w / w) sodium alginate solution and a 5% (w / w) calcium chloride solution were sprayed into a fluidized bed for coating. The amount of sodium alginate and calcium chloride sprayed was controlled to be 0.15 kg each. After complete drying, a micron-sized folic acid preparation was obtained.

[0057] The scanning electron microscope image of porous starch is shown below. Figure 1 As shown, the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the micron-sized folic acid formulation in this embodiment are as follows: Figure 2 and Figure 3 As shown. According to Figures 1-3 It is known that the average particle size of porous starch is 5-10 micrometers, while the average particle size of the micron-sized folic acid preparation after adsorption is about 200-300 micrometers. The interior of porous starch is completely filled with the folic acid liquid dispersion system. Transmission electron microscopy shows that the folic acid particles in the liquid dispersion system are small enough to be unobservable.

[0058] The specific surface area of ​​porous starch, as determined by BET, is 4.011 m². 2 / g indicates that the porous starch adsorbent has a strong adsorption capacity.

[0059] A certain amount of the micron-sized folic acid preparation of this embodiment was spread evenly on the texture analyzer platform and compressed at a speed of 0.01 mm / s for 90%. The 70% deformation pressure was measured to be 148.56 N, indicating that the micron-sized folic acid preparation of this embodiment has strong compressive strength, good particle integrity, and is not easily damaged, making it suitable for further processing into tablets, capsules, suspensions, or other dosage forms. The scanning electron microscope image of Example 1 after compression is shown below. Figure 10 As shown, the particles are relatively intact and undamaged, indicating that they have good compressive stability.

[0060] Using 70wt% maltitol solution as a dispersant, both the folic acid technical and the micron-sized folic acid formulation of this embodiment were dispersed in the 70wt% maltitol solution at a folic acid concentration of 0.5wt%. The pH was adjusted to 3, and accelerated comparative evaluations were conducted at 30℃ and 70℃. The stability of the micron-sized folic acid formulation in aqueous processing environments was reflected by measuring the folic acid retention rate at different times, and its hydrophobic effect was evaluated. The results showed that the micron-sized folic acid formulation of this embodiment exhibited excellent stability under both room temperature and high-temperature aqueous processing environments, with significantly reduced dissolution and degradation, as shown in Table 1.

[0061] Table 1. Stability test results of the micron-sized folic acid formulation in Example 1

[0062] Example 2 215g of vitamin E, 43g of soybean oil, and 22g of beeswax were ground and dispersed at 70℃ for 60 minutes to obtain a liquid dispersion system. The liquid dispersion system was then added to 150g of porous cellulose for adsorption. After complete adsorption, a 10% mass concentration of zein in an ethanol / water solution (ethanol:water = 7:3, volume ratio) was sprayed into a fluidized bed for coating. The amount of zein sprayed was controlled to be 5% of the mass of vitamin E. After complete drying, a micron-sized vitamin E preparation was obtained.

[0063] The scanning electron microscope image of porous cellulose is shown below. Figure 4 As shown, the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the micron-sized vitamin E formulation in this embodiment are as follows: Figure 5 and Figure 6 As shown. According to Figures 4-6 It is known that the average particle size of porous cellulose is 50-100 micrometers, and the average particle size of the micron-sized vitamin E preparation after adsorption is about 100-150 micrometers. The interior of porous cellulose is completely filled by the vitamin E liquid dispersion system, and transmission electron microscopy shows that there are a large number of nanoscale adsorption spaces inside the porous cellulose.

[0064] The specific surface area of ​​porous cellulose was determined to be 26.338 m² / g by BET analysis. 2 / g indicates that the porous cellulose adsorbent has a strong adsorption capacity.

[0065] A certain amount of the micron-sized vitamin E formulation of this embodiment was spread evenly on the texture analyzer platform and compressed at a speed of 0.01 mm / s for 90%. The measured 70% deformation pressure was 30.52 N, indicating that the micron-sized vitamin E formulation of this embodiment has strong compressive strength, good particle integrity, and is not easily damaged, making it suitable for further processing into tablets, capsules, suspensions, or other dosage forms. The scanning electron microscope image after compression in Example 2 is shown below. Figure 11 As shown, the particles are relatively intact and undamaged, indicating that they have good compressive stability.

[0066] Using 70 wt% maltitol solution as a dispersant, both the vitamin E technical and the micron-sized vitamin E formulation of this embodiment were dispersed in the maltitol solution at a vitamin E concentration of 0.5 wt%. The pH was adjusted to 3, and accelerated comparative evaluations were conducted at 30°C and 70°C. The stability of the micron-sized vitamin E formulation in a sugar-containing aqueous solution processing environment was reflected by measuring the vitamin E retention rate at different times. The results showed that the micron-sized vitamin E formulation of this embodiment exhibited excellent stability under both room temperature and high-temperature water processing environments, with significantly reduced dissolution and degradation, as shown in Table 2.

[0067] Table 2. Stability test results of the micron-sized vitamin E formulation in Example 2

[0068] Example 3 First, 100g of paclitaxel and 400g of corn oil were ground and dispersed at 30℃ for 30 minutes. Then, 40g of carnauba wax was added at 90℃ and the mixture was ground and dispersed for another 10 minutes to obtain a liquid dispersion system. The liquid dispersion system was then added to 130g of porous zein for adsorption. After complete adsorption, a 0.1% chitosan solution (1% acetic acid aqueous solution as solvent) was sprayed into a fluidized bed for coating. The amount of chitosan sprayed was controlled to be 3% of the mass of paclitaxel. After complete drying, a micron-sized paclitaxel formulation was obtained.

[0069] The scanning electron microscope image of porous zein is shown below. Figure 7 As shown, the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the micron-sized paclitaxel formulation in this embodiment are as follows: Figure 8 and Figure 9 As shown. According to Figures 7-9 It is known that the average particle size of porous zein is 10-20 micrometers, while the average particle size of the micron-sized paclitaxel formulation after adsorption is approximately 50-100 micrometers. The interior of the porous zein is completely filled with the paclitaxel liquid dispersion system. Figure 9 The liquid dispersion system showed that paclitaxel had a length of less than 1 micrometer and a diameter of approximately 10-100 nanometers, which is consistent with the characteristics of nanomedicines.

[0070] The specific surface area of ​​porous zein protein was determined to be 25.018 m² / g. 2 / g indicates that the porous zein adsorbent has a strong adsorption capacity.

[0071] A certain amount of the micron-sized paclitaxel formulation of this embodiment was spread evenly on the texture analyzer platform and compressed at a speed of 0.01 mm / s for 90%. The measured 70% deformation pressure was 43.32 N, indicating that the micron-sized paclitaxel formulation of this embodiment has strong compressive strength, good particle integrity, and is not easily damaged, making it suitable for further processing into tablets, capsules, suspensions, or other dosage forms. The scanning electron microscope image after compression in Example 3 is shown below. Figure 12 As shown, the particles are relatively intact and undamaged, indicating that they have good compressive stability.

[0072] Using 70 wt% maltitol solution as a dispersant, both paclitaxel technical and the micron-sized paclitaxel formulation of this embodiment were dispersed in maltitol solution at a concentration of 0.5 wt% paclitaxel. The pH was adjusted to 3, and accelerated comparative evaluation was conducted at 30℃ and 70℃. The stability of the micron-sized paclitaxel formulation of this embodiment in a sugar-containing aqueous solution processing environment was reflected by measuring the paclitaxel content retention rate at different times. The results showed that the micron-sized paclitaxel formulation of this embodiment had excellent stability under both room temperature and high temperature water processing environments, with significantly reduced dissolution and degradation, as shown in Table 3.

[0073] Table 3. Stability test results of the micron-sized paclitaxel formulation in Example 3

[0074] Example 4 A micron-sized active pharmaceutical formulation has the following composition as shown in Table 4. Samples 4-1 and 4-2 differ from Example 1 only in the proportion of their components; samples 4-3 and 4-4 differ from Example 2 only in the proportion of their components; and samples 4-5 and 4-6 differ from Example 3 only in the proportion of their components.

[0075] Table 4 Formulation Composition of Example 4

[0076] Comparative Examples 1-6 The only difference between Comparative Examples 1 and 2 and Example 1 is the composition of the oil dispersant.

[0077] The only difference between Comparative Example 3 and Example 1 is the mass ratio of edible oil and oil gelling agent.

[0078] The only difference between Comparative Example 4 and Sample 4-1 in Example 4 is the mass ratio of edible oil and oil gelling agent.

[0079] The only difference between Comparative Example 5 and Example 1 is that no oil dispersant was added, and the amount of biomass porous adsorbent was still 3 kg, while all other conditions were the same.

[0080] The only difference between Comparative Example 6 and Example 1 is that no coating was performed; all other conditions were the same.

[0081] The specifics are shown in Table 5.

[0082] Table 5. Formulation composition of Comparative Examples 1-6

[0083] Comparative Example 7 The only difference from Example 1 is the preparation process. In Example 1, the biomass porous adsorbent is first mixed with the active drug, and then mixed with the oil dispersant. The coating process remains the same, as follows: 0.3 kg of folic acid was added to 3 kg of porous starch for adsorption. After complete adsorption, 1 kg of sunflower seed oil and 0.1 kg of rice bran wax were added. The mixture was ground at 80°C for 45 minutes. Then, a 1% sodium alginate solution and a 5% calcium chloride solution were sprayed into a fluidized bed for coating. The amount of sodium alginate and calcium chloride sprayed was controlled to be 0.15 kg each. After complete drying, a micron-sized folic acid preparation was obtained.

[0084] Test Example 1: In Vitro Simulated Digestion Test The technical grade drugs and micron-sized active pharmaceutical formulations of Examples 1-4 and Comparative Examples 1-7 were subjected to in vitro simulated digestion comparisons. Simulated gastric juice was used for digestion for 2 hours, and simulated intestinal juice for digestion for 24 hours. The release rate was calculated by measuring the content of active pharmaceutical ingredients in the digestive fluids. The folic acid, vitamin E, and paclitaxel technical grade drugs corresponding to each example and comparative example were the same.

[0085] Preparation of artificial gastric fluid: Accurately measure 3.84 mL of 37% concentrated HCl, 5 mL of Tween-80, 86 μL of α-amylase with an activity of 150,000 U / mL, and 100 mg of amylase with an activity of 100,000 U / g, and add them to 500 mL of deionized water. Then add more deionized water to make up the volume to 1000 mL. Adjust the pH to 1.5 with 1 mol / L HCl and 1 mol / L NaOH. This is the artificial gastric fluid.

[0086] Preparation of artificial intestinal fluid: Add 2.72g of potassium dihydrogen phosphate to the above 400 mL of artificial gastric fluid, and adjust the pH to 7.4 with 1mol / L NaOH to obtain artificial intestinal fluid.

[0087] Digestion experiment: Take 5 mg of active drug (original drug) or a micron-sized active drug preparation containing the same mass of active drug and add it to 400 mL of artificial gastric juice. Place it in a magnetic stirrer at 37℃ and stir at 100 r / min. The whole process is carried out in a constant temperature water bath. Samples can be taken for testing and artificial gastric juice can be added during the process. Digestion lasts for 2 hours.

[0088] After digestion with artificial gastric juice is complete, add 2.72g of potassium dihydrogen phosphate and adjust the pH to 7.4 with 1mol / L NaOH. Then continue digestion under the above conditions for 24 hours. Samples can be taken and artificial intestinal juice can be added during the process.

[0089] The results are shown in Table 6.

[0090] Table 6 Results of in vitro simulated digestive drug release rate test

[0091] As shown in Table 6, under gastric juice conditions, the micron-sized active pharmaceutical formulations of the present invention are basically not released, but the release rate of their corresponding original drugs exceeds 50%, and they are even almost completely digested.

[0092] In the intestinal fluid environment, folic acid and vitamin E technical materials showed significant oxidative degradation, while the release of paclitaxel technical material did not increase significantly compared to the gastric fluid environment, indicating that paclitaxel technical material had been significantly degraded in the gastric fluid environment; however, the micron-sized active pharmaceutical formulation of the present invention showed no significant oxidative degradation, and basically achieved complete release, with a final release rate significantly higher than that of the technical material.

[0093] Comparisons 1-4 with Example 1 or Example 4 show that by adding edible oils and oleogloss agents in specific proportions, the release of the drug into gastric juice can be reduced, while oxidative degradation in the intestinal fluid environment can be decreased, and the release into the intestinal fluid can be promoted, thus improving bioavailability. However, excessively high proportions of edible oils as oil dispersants lead to poor protective effects and increased gastric juice release; excessively high proportions of oleogloss agents as oil dispersants result in excessively high processing temperatures, significant loss of active pharmaceutical ingredients during processing, and although gastric juice release is less, the final release rate of the active pharmaceutical ingredient is reduced.

[0094] Comparing Comparative Example 5 with Example 1, it can be seen that the oil dispersant is a necessary carrier for the formation of an effective protective system for the active drug; comparing Comparative Examples 6 and 7 with Example 1, it can be seen that the coating of the formulation and the order of addition of raw materials during the preparation process have a significant impact on the digestion and release of the formulation.

[0095] Test Example 2: Compression Test Referring to the test methods described in Examples 1-3, a texture apparatus was used to perform compressive strength tests. The compressive strength was measured at a speed of 0.01 mm / s and 90%. The 70% deformation pressure of Examples 4 and Comparative Examples 1-7 was measured, and the results are shown in Table 7.

[0096] Table 7 Results of the compressive strength test

[0097] Test Example 3: Stability Test of Processing in Aquatic Environment Referring to the test methods described in Examples 1-3, 70wt% maltitol solution was used as the dispersant, and the concentrations of the active pharmaceutical ingredient and the micron-sized active pharmaceutical ingredient alcohol formulation were 0.5wt%. The pH was adjusted to 3, and accelerated comparative evaluations were conducted at 30℃ and 70℃ to determine the retention rate of the active pharmaceutical ingredient at different times. The test results of Example 4 and Comparative Examples 1-7 are shown in Table 8. The results indicate that the coating of the formulation and the order of addition of raw materials during the preparation process significantly affect the aqueous processing stability of the formulation. Improper process selection can lead to partial oxidation of the active pharmaceutical ingredient during processing, resulting in aqueous processing stability that is even worse than that of the active pharmaceutical ingredient.

[0098] Table 8 Results of water environment processing stability test

[0099] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A micron-sized active pharmaceutical formulation, characterized in that, It is composed of an active drug, a biomass porous adsorbent, an oil dispersant, and a coating agent, wherein the active drug is folic acid; The oil dispersant is a mixture of edible oil and oil gelling agent, with a mass ratio of 1:0.1-1; The edible oil is sunflower seed oil, and the oil gelling agent is rice bran wax; The coating agent is at least one of the following: a mixture of sodium alginate and calcium chloride, chitosan, and zein. The biomass porous adsorbent is at least one of porous starch, porous cellulose and porous zein, and the average particle size of the biomass porous adsorbent is 1-100 μm. The mass ratio of active drug to oil dispersant is 1:0.5-5; The mass ratio of the biomass porous adsorbent to the total mass of the active drug and the oil dispersant is 1:0.1-5; the mass ratio of the coating agent to the active drug is 1-100:

100. The method for preparing the micron-sized active pharmaceutical formulation includes the following steps: (1) The active drug is mixed with an oil dispersant to obtain a liquid dispersion system; (2) The biomass porous adsorbent is mixed with a liquid dispersion system to obtain the adsorption product; (3) Prepare a coating solution with the coating agent, use the coating solution to coat the adsorption product obtained in step (2), and dry it to obtain the product. In step (1), the active drug and the oil dispersant are mixed and then ground. The grinding temperature is 30-90℃ and the grinding time is 40-60min.

2. The micron-sized active pharmaceutical formulation according to claim 1, characterized in that, When the coating agent is zein, the biomass porous adsorbent does not contain porous zein.

3. The micron-sized active pharmaceutical formulation according to any one of claims 1-2, characterized in that, The micron-sized active pharmaceutical preparation is in the form of granules, tablets, capsules, or suspensions.

4. The method for preparing the micron-sized active pharmaceutical formulation according to any one of claims 1-2, characterized in that, The steps include the following: (1) The active drug is mixed with an oil dispersant to obtain a liquid dispersion system; (2) The biomass porous adsorbent is mixed with a liquid dispersion system to obtain the adsorption product; (3) Prepare a coating solution with the coating agent, use the coating solution to coat the adsorption product obtained in step (2), and dry it to obtain the product. In step (1), the active drug and the oil dispersant are mixed and then ground. The grinding temperature is 30-90℃ and the grinding time is 40-60min.

5. The preparation method according to claim 4, characterized in that, In step (1), after the active drug is mixed with the oil dispersant, the average particle size of the active drug is made to reach 0.1-1 μm by grinding; in step (3), the concentration of the coating solution is 10-100% of the saturation concentration; after drying in step (3), it is further processed into granules, tablets, capsules or suspensions.

Citation Information

Patent Citations

  • Film-coated paclitaxel nano-drug, and preparation method and application thereof

    CN104586750A

  • Preparation method of L-5-methyl tetrahydrofolate microcapsule

    CN110237046A

  • Folic acid tablet and preparation process thereof

    CN117752620A

  • Preparation method of high-stability vitamin E soft capsule

    CN118453533A

  • Folic acid tablet with low oxidation impurity content and preparation method of folic acid tablet

    CN119112901A